-3=v-6+3

Simple and best practice solution for -3=v-6+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=v-6+3 equation:



-3=v-6+3
We move all terms to the left:
-3-(v-6+3)=0
We add all the numbers together, and all the variables
-(v-3)-3=0
We get rid of parentheses
-v+3-3=0
We add all the numbers together, and all the variables
-v=0
v=0/-1
v=0

See similar equations:

| 6(-5-4x)=-174 | | 6xx5=25 | | 6x*5=25 | | 15=6-6x-3 | | 8-3f=5 | | n+0=1 | | 3x+7-2=10 | | 66+m=127 | | 12x+3(3x+6)=x+8 | | -5(v+4)+2v+5=8v+8 | | c-8/3=4c+6/4 | | 18=1-5x-3 | | 4y=−4.2 | | 1.6+3.2x=2.4x+2.7 | | y^2-y+90=0 | | 7a-11=66 | | 2y+10+3y-40=170 | | x-(3x-5)=4-(3x+3) | | .5x+7=17 | | 7+12x=79 | | 3x/9-4x/3=4 | | 0.20(y-7)+0.06y=0.16y-0.6 | | 0.3x+0.25x+x/3=x+1.5 | | -5w+30+25w=60 | | .5(x+5)=34 | | 5+14a=9a-10 | | 37x-20-7x=40 | | −14t=−1 | | 60a+10=70 | | -4z-4+7+z=22 | | 5x/0.5=20 | | 2/3x+5=1/4x-10 |

Equations solver categories